3-Dimensional wireless sensor network localization: A review - Najib, Y.N.A. (American Institute of Physics Inc., 2016)
The proliferation of wireless sensor network (WSN) has shifted the focus to 3-Dimensional geometry rather than 2-Dimensional geometry. Since exact location of sensors has been the fundamental issue in wireless sensor network, node localization is essential for any wireless sensor network applications. Most algorithms mainly focus on 2-Dimensional geometry, where the application of this algorithm will decrease the accuracy on 3-Dimensional geometry. The low rank attribute in WSN's node estimation makes the application of nuclear norm minimization as a viable solution for dimensionality reduction problems. This research proposes a novel localization algorithm for 3-Dimensional WSN which is nuclear norm minimization. The node localization is formulated via Euclidean Distance Matrix (EDM) and is then optimized using Nuclear-Norm Minimization (NNM). Â© 2016 Author(s).